Pacing, exercise intensity, and technique by performance level in long-distance cross-country skiing - Stoeggl, T. L.; Hertlein, M.; Brunauer, R.; Welde, B.; Andersson, E. P.; Swaren, M. (Frontiers in Physiology, 2020)
Introduction Long-distance cross-country skiing (XCS) has gained increased popularity within the past decades. However, research about long-distance XCS is limited; therefore, the aim of this study was to analyze the intensity distribution, technique application, and pacing strategies during long-distance XCS racing. Methods Heart rate (HR) and section skiing speeds of 9 elite (ranked 1-100) and 10 amateur skiers (ranked 101-1,500) during the 90-km Vasaloppet race were collected. In addition, during the first uphill, the first 1,000 skiers were video-recorded to analyze the applied skiing strategy (e.g. grip-waxed skis versus exclusive double poling). Results Mean race intensity was 82% of maximal HR and was not different between performance groups even though elite skiers skied similar to 15% faster than amateurs. There was an interaction effect of section x group with a pronounced decrease in HR in amateurs compared with more even pacing in elite skiers (0.13 vs. 0.04% decrease/km) and skiing at higher percentage in the high-intensity zones in elite compared with amateurs (46 vs. 24%). Ninety-eight percent of the top 100 skiers and 59% of the first 1,000 skiers used exclusively double poling. Conclusion Elite and amateur skiers ski at comparable mean race exercise intensity, but they have clear differences in skiing speed. The difference in the pacing profiles between elite and amateur skiers (more even vs. distinct positive pacing) demonstrate the greater capacity of the former with respect to physiological capacity and highlights that amateurs seem to start too fast according to their capacities. The exclusive application of the double poling technique is no longer a phenomenon of elite skiers but is widely used among the top 1,000 ranked skiers.